STUDENTS’ PERSPECTIVE ON LECTURERS’ STRATEGIES IN TEACHING READING - Parwati, Agustin; Khoirot, Umdatul (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
Nowadays, especially in STKIP PGRI Tulungagung, the reading interest of the students is varied. But, they realize that reading is important. But, there were opinion from students that the lecturers’ strategies can affect their interest in reading or in reading lesson. The aim of this study is to know how students’ perspectives on lecturers’ strategies in teaching reading. For that reason, it does not analyze the way students learn during reading lessons. But, it just analyzed from the students’ opinion. The subjects of this study are students from semester two and students from semester four. There are two instruments employed: questionnaires (close and open questionnaires) and interviews. From the data obtained, the results of close and open questionnaires, most students from second semester and fourth semester have thought that in reading activity, it is not only focus on pronunciation. Then, they also thought that reading activity is very important to increase their knowledge even to add vocabulary. Furthermore, they agreed if reading is beneficial to add vocabulary and knowledge. Then, most of them said that the strategy used by lecturer in teaching reading is good and acceptable.